EXTERNAL ECONOMIC ACTIVITY OF SOCIO-ECONOMIC SYSTEMS: STATE, MANAGEMENT AND ASSESSMENT - TYURINA, Nila; NAZARCHUK, Tetyana; PETYAK, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article outlines the general problems related to the analysis of the current state, the formation of a management system, and the assessment of the development potential of foreign economic activity (FEA) of socio-economic systems under modern conditions. The author’s interpretation of the basic categories of foreign economic activity for socio-economic systems at different levels of governance is proposed. The dynamics of export-import activity of the macro-level socio-economic system over a long period have been examined; the main factors causing negative trends have been identified, as well as the implemented opportunities for overcoming the crisis and the projected prospects for further development. Foreign economic activity is considered an indicator of economic openness and an instrument for ensuring economic security. The purpose of effective management of foreign economic activity at the macro level has been defined, a comprehensive management system has been developed, and the key directions of its development in the post-war period have been determined. The components and priorities of the management system of FEA entities have been outlined, with an emphasis on innovation and environmental components. The structure of the general system for assessing the development potential of FEA of socio-economic systems at the macro and micro levels has been formed, and the interdependence and correlation links between different levels of governance have been identified. The prospects and relevance of further scientific research in the specified direction have been substantiated.
Keywords: management; foreign economic activity; export potential; development potential; evaluation of foreign economic activity; socio-economic system; enterprise